The Relevance of Serum Ghrelin Concentration to Severity of Acute Pancreatitis - Lee, Se Hyung (The Korean Society of Gastroenterology; the Korean Society of Gastrointestinal Endoscopy; the Korean Association for the Study of the Liver; the Korean Society of Neurogastroenterology and Motility; Korean Association for the Study of Intestinal Diseases; Korean College of Helicobacter and Upper Gastrointestinal Research; Korean Society of Pancreatobiliary Diseases, 2010)
BACKGROUND/AIMS: Ghrelin has recently been reported as exerting a protective effect in the damaged pancreas in rats. We investigated the correlation between severity of acute pancreatitis and serum ghrelin concentrations. METHODS: Blood samples were collected three times (at admission, after 48 hours, and at discharge) from patients admitted with acute pancreatitis. We divided the patients into nonrisk and risk groups. The risk group was defined as the presence of at least one of following risk factors for severe acute pancreatitis: Ranson's score ≥3, acute physiology and chronic health evaluation (APACHE) II score ≥8, C-reactive protein (CRP) ≥150 mg/L, and CT severity index (CTSI) ≥4. Serum ghrelin concentrations were measured with RIA kit and analyzed based on clinical and biochemical parameters. RESULTS: A total of 53 patients was enrolled in this study: 28 in the nonrisk group and 25 in the risk group. At admission, the ghrelin concentration was significantly higher in the risk group (286.39±272.19 vs 175.96±138.87 pg/mL [mean±SD], p=0.049). However, the ghrelin concentration did not differ significantly between the two groups after 48 hours (p=0.450) and at discharge (p=0.678). The overall ghrelin concentration was significantly lower at admission than at discharge (240.65±247.96 vs 369.41±254.27 pg/mL, p=0.001). CONCLUSIONS: Patients with risk factors for severe acute pancreatitis have higher serum ghrelin concentrations.